Manajemen Pesantren: Studi Telaah Tentang Kurikulum dan Pembelajaran di Pondok Modern Darussalam Gontor-Ponorogo - Munir, Miftahul (Didaktika Religia, 2015)
The study is intended to examine the curriculum and teaching learning in Pondok Modern Darussalam Gontor-Ponorogo. A process of structuring and management of education institutions like Pesantren involving human and non-human in achieving the goal of Pesantren is the central theme of the study. This research is expected to contribute to society, both theoretically and practically. This study is descriptive qualitative. The curriculum at Pondok Modern Darussalam Gontor integrates religious knowledge and the kawniyah science, and thus they cannot be separated from the basisÂ  and religious values. On the contrary, the teaching of religious knowledge should be in line with general scientific developments.